Are Health Shocks Different? Evidence from a Multi-Shock Survey in Laos - Wagstaff, Adam; Lindelow, Magnus (2012)
In Laos health shocks are more common than most other shocks and more concentrated among the poor. They tend to be more idiosyncratic than non-health shocks, and are more costly, partly because they lead to high medical expenses, but also because they lead to income losses that are sizeable compared with the income losses associated with non-health shocks. Health shocks also stand out from other shocks in the number of coping strategies they trigger: they are more likely than non-health shocks to trigger assistance from a nongovernmental organization and other households, dis-saving, borrowing, asset sales, an early harvest, the pawning of possessions, and the delaying of plans; by contrast, they are less likely to trigger assistance from government. Consumption regressions point to only limited evidence of households not being able to smooth consumption in the face of any shock. However, these results contrast with households' own assessments of the welfare impacts of shocks. The majority said they had to cut back consumption following a shock and that shocks considerably affected their welfare. Only health shocks are worse than a drought in terms of the likelihood of a family being forced to cut back consumption and in terms of the shock affecting a family's well-being "a lot." The poor are especially disadvantaged in terms of the greater damage that health shocks inflict on household well-being. Health shocks stand out too in leading to a loss of human capital: household members experiencing a health shock did not recover their former subjective health following the health shock, losing, on average, 0.6 points on a 5-point scale. The wealthier and better educated are better able to limit the health impacts of a health shock; the data are consistent with this being due to their greater proximity to a health facility.